2007
DOI: 10.3892/ijo.30.6.1441
|View full text |Cite
|
Sign up to set email alerts
|

DMBT1 is frequently downregulated in well-differentiated gastric carcinoma but more frequently upregulated across various gastric cancer types

Abstract: Well-differentiated gastric carcinomas are considered to represent a distinct entity emerging via specific molecular changes different from those found in other gastric carcinoma types. The gene deleted in malignant brain tumours 1 (DMBT1) at 10q25.3-q26.1 codes for a protein presumably involved in cell differentiation and protection and has been proposed as a candidate tumour suppressor for brain and epithelial cancer. One study reported a loss of DMBT1 expression in 12.5% (5/40) of gastric cancer samples. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…7A). The mRNA expression level of Dmbt1, which has a function in epithelial cell differentiation and gastric mucosal protection (24), was highly increased between 20 and 52 weeks postinfection in the fundus of H. heilmannii-and H. pylori-infected mice (Fig. 7B).…”
Section: Resultsmentioning
confidence: 94%
“…7A). The mRNA expression level of Dmbt1, which has a function in epithelial cell differentiation and gastric mucosal protection (24), was highly increased between 20 and 52 weeks postinfection in the fundus of H. heilmannii-and H. pylori-infected mice (Fig. 7B).…”
Section: Resultsmentioning
confidence: 94%
“…Infrequent mutation of DMBT1 has been reported in astrocytic tumors (19). In addition, upregulation of DMBT1 has been reported in specific glioblastomas (20) and carcinomas of the stomach (21) and lung (22). These diverse observations imply complex roles of DMBT1 in carcinogenesis.…”
Section: Deleted In Malignant Brain Tumor 1 Is a Novel Prognostic Marmentioning
confidence: 99%
“…Prakobphol et al [89] using a proteomic approach demonstrated that SAG was identical to the previously identified and cloned lung Scavenger Receptor Cysteine-Rich (SRCR) glycoprotein gp340, which is a product of the DMBT1 gene. There is an extensive literature relating to DMBT-1 functioning as a tumor suppressor in a variety of epithelial derived tumors [9092]. …”
Section: Introductionmentioning
confidence: 99%